Standardization for Mechanized Information Systems - Vij, V. P.; Bahl, A. K. (Journal of Information and Knowledge, 1986)
Standardization offers solutions for repetitive problems. Historically, it has been applied in the fields of activity that were most important at that time but its importance increased after the industrial revolution. Standardization of writing, galeys and paper sizes was done because of the need for, and generation of, printed matter. Due to the excessive amount of written information, and greater demands of users, information scientists are increasingly utilizing modern technological aids like computers for information processing. Standardization, therefore, is necessary for processes, practices and materials used in this area to reduce costs, minimize effort, save time and conserve materials. Interaction between man and computers has three phases; man-machine, machine-machine and machine-man. In the first phase areas requiring standardization include programming languages, information handling procedures and input of information in data-bases. To facilitate exchange, further, standardization of equipment is also necessary while in the machine-man phase standardization's scope is limited to sizes, printing and format of output. For networks, to avoid duplication of work, document processing has to be rationalized too to control the data bases. This can be done by standardizing indexing, procedures and vocabulary as has been done by ISONET members. Standards have been formulated at the International level by ISO in the field of documentation and information science as well as mechanized information processing systems. ISI is also formulating standards in these areas, keeping in view the national scene and the need for uniformity at the global level. It is hoped that standards would be used while venturing into mechanized information systems for reaping the benefits that accrue from their use.